KEANEKARAGAMAN IKAN DI SUNGAI BATANG DURIAN KABUPATEN AGAM SUMATERA BARAT - Cindy Cindy; Indra Junaidi Zakaria; Nofrita Nofrita (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
Human activities along Batang Durian River can affect the diversity of aquatic organism, especially fishes. Fish diversity is the trophic characteristic based on its biological organisms that determine community structure. The research had been conducted from Mei to September 2016 to analyze the type of abundance, fish diversityand physical-chemical aspects of aquatic body. The research used survey method. Furthermore, the location and sampling effort were determined with purposive random sampling technique. Sample collection was set during 1 hour of catching till no more new species found in the three sampling location. The result revealed there were 9 species with 46 individuals in Batang Durian River. Diversity index in Batang Durian River was classified as medium with the distribution was even and no species dominated. The physical-chemical aspects of Batang Durian River were supposed to be able to support the live of aquatic organisms within. Human activities along the river body was fairly affecting fish diversity in it.